2013
DOI: 10.1007/s10695-012-9763-5
|View full text |Cite
|
Sign up to set email alerts
|

Dietary taurine can improve the hypoxia-tolerance but not the growth performance in juvenile grass carp Ctenopharyngodon idellus

Abstract: This study was conducted to evaluate the effects of dietary taurine, as a feed additive, on the hypoxia-tolerance and growth performance of the juvenile grass carp Ctenopharyngodon idellus, one of the most important and intensively cultured freshwater fish, with the largest production in China. Graded levels of taurine (0, 0.5, 1, 1.5, 2 and 2.5 g kg(-1) dry diet) were fed to grass carp juveniles (mean weight: 5.26 ± 0.03 g) for 8 weeks. The survival time during acute hypoxia increased as dietary levels of tau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 37 publications
3
17
0
Order By: Relevance
“…Positive health effects were also found in grass carp: although taurine has no effect on growth in this species, Yang et al (2013) showed that lower hemolysis rate was correlated with acute hypoxia tolerance. Thus, it may still be beneficial to supplement taurine in grass carp or other non-carnivorous species based on health aspects despite a lack of a growth response with low taurine diets.…”
Section: Accepted Manuscriptmentioning
confidence: 86%
“…Positive health effects were also found in grass carp: although taurine has no effect on growth in this species, Yang et al (2013) showed that lower hemolysis rate was correlated with acute hypoxia tolerance. Thus, it may still be beneficial to supplement taurine in grass carp or other non-carnivorous species based on health aspects despite a lack of a growth response with low taurine diets.…”
Section: Accepted Manuscriptmentioning
confidence: 86%
“…Interestingly, taurine was reported to improve the hypoxia tolerance of grass carp (Ctenopharyngodon idellus) (Yang, Tian, Huang, Liang, & Liu 2013). Six taurine level were set under the lower fish meal in the experiment to research the effect on growth performance, and to highlight the importance of dietary taurine on antioxidant status and immune response of M. albus.…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al () found that 0.2% taurine in a commercial diet (the content of taurine in the commercial diet was 0.245%) had no improving effect on the growth of shrimp, L. vannamei . In addition to its role in growth performance, dietary taurine could improve the hypoxia‐tolerance ability of juvenile grass carp (Yang et al ), increase antioxidative capacity of Chinese soft‐shelled turtles (Hou et al ), and alleviate cadmium‐induced oxidative stress in freshwater catfish (Kumar et al ). Therefore, as a kind of feed additive, taurine has been getting more and more emphasis in research on aquatic animals.…”
mentioning
confidence: 99%